Influence of fatty chain length and starch composition on structure and properties of fully substituted fatty acid starch esters. (15th May 2017) - Vanmarcke, Audrey; Leroy, Lise; Stoclet, Gregory; Duchatel-Crépy, Lucie; Lefebvre, Jean-Marc; Joly, Nicolas; Gaucher, Valérie
Highlights: Characteristics of FASEs depend of both fatty chain length and starch origin. Layered type organization: starch chain planes are separated by alkyl chains. FASEs with C8 and C12 side chains are amorphous. Fatty chains for FASE with C16 side chains partially crystallize. Improvement of material ductility with amylose content for C8 and C12 chains. Abstract: A series of almost fully substituted Fatty Acid Starch Esters (FASEs) has been obtained in a homogeneous LiCl/DMAc medium by grafting octanoyl (C8), lauroyl (C12) and palmitoyl (C16) chlorides onto 3 starch species: Amylo-Maize, Potato and Waxy Maize. Structure-property relationships of FASEs are investigated as a function of both fatty acid chain length and amylose/amylopectin ratio of the starch. The structural study has revealed a layered type organization in which starch chain planes are separated by fatty chains. The latter are interpenetrated and/or tilted for FASE-C16 whatever the origin of the starch is, and fatty chains partially crystallizes into a structure with hexagonal symmetry. FASEs with C8 and C12 side chains are totally amorphous. The mechanical behavior of FASEs is shown to depend on both side chain length and amylose/amylopectin ratio, and an increase in material ductility is observed at increasing amylose content for C8 and C12 side chains.